Culturally appropriate pedagogy in a bilingual family literacy programme. (20th February 2014) - Friedrich, Nicola; Anderson, Jim; Morrison, Fiona
Abstract Researchers have documented bilingual family literacy programmes in terms of their structure and programming as well as their effect on children's language and literacy development and parents' ability to support such development within the home. What is missing from the discussion is a description of how facilitators mediate understanding within the programme. The purpose of this article is to describe how facilitators working with Karen and Iranian families mediated parents' understanding of the key concepts within the parent‐only segment of a bilingual family literacy programme for immigrant and refugee families in western Canada. Drawing principally from observational field notes at two sites of the programme, we describe the activities and instruction that took place during the introduction to the session, Rhythm, Raps and Rhymes. Supporting data were drawn from a larger 3‐year study. Our findings indicate that the facilitators at both sites mediated the parents' understanding of the benefits of rhythm and rhyme to early literacy by using culturally familiar and relevant content delivered in both the first language of the community and in English, and by drawing from culturally familiar pedagogical practices. Results of this study have implications for the delivery of family literacy programmes within culturally diverse communities.